Fluorene- and fluorenone-based molecules as electron-transporting SAMs for photovoltaic devices - Svirskaite, Lauryna Monika; Kasparavičius, Ernestas; Steponaitis, Matas; Grzibovskis, Raitis; Franckevičius, Marius; Katerski, Atanas; Naujokaitis, Arnas; Karazhanov, Smagul; Gopi, Sajeesh Vadakkedath; Aizstrauts, Arturs; Vembris, Aivars; Getautis, Vytautas; et al. (Royal Society of Chemistry, 2024)
New semiconductors containing fluorene or fluorenone central fragments along with phosphonic acid anchoring groups were synthesized and investigated as electron transporting materials for possible application in photovoltaic devices. These derivatives demonstrate good thermal stability and suitable electrochemical properties for effective electron transport from perovskite, Sb2S3 and Sb2Se3 absorber layers. Self-assembled fluorene and fluorenone electron-transporting materials have shown improved substrate wettability, indicating bond formation between monolayer-forming compounds and the ITO, TiO2, Sb2S3, or Sb2Se3 surface. Additionally, investigated materials have compatible energetic band alignment and can passivate perovskite interface defects, which makes them interesting candidates for application in the n-i-p structure perovskite solar cell. © 2024 The Royal Society of Chemistry. --//-- This is an open-access article Svirskaite, Lauryna Monika; Kasparavičius, Ernestas; Steponaitis, Matas; Grzibovskis, Raitis; Franckevičius, Marius; Katerski, Atanas; Naujokaitis, Arnas; Karazhanov, Smagul; Gopi, Sajeesh Vadakkedath; Aizstrauts, Arturs; Vembris, Aivars; Getautis, Vytautas; Malinauskas, Tadas, "Fluorene- and fluorenone-based molecules as electron-transporting SAMs for photovoltaic devices", RSC Adv., 2024, volume 14, issue 21, pages 14973-14981, doi 10.1039/D4RA00964A published under CC BY-NC licence.
The \u2018Development of Semi-Transparent Bifacial Thin Film Solar Cells for Innovative Applications\u2019 benefits from a \u20AC1\u2009000\u2009000 grant from Iceland, Liechtenstein and Norway through EEA Grants. The aim of the project is to develop materials for semi-transparent bifacial cost-effective solar cells, which operate in full and faint sunlight, as well as in backlit, snow-reflected conditions. Project contract with the Research Council of Lithuania (LMTLT) No. S-BMT-21-1 (LT08-2-LMT-K-01-003). M. F. acknowledges funding from the Research Council of Lithuania (grant agreement No. P-MIP-22-210). Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART²
Keywords: Research Subject Categories::NATURAL SCIENCES